Aspectos legais e regulatórios da conta de consumo de combustíveis dos sistemas isolados: uma análise crítica - Magalhães, Pedro Coelho de Souza Monteiro (2009)
In accordance with the objectives of Brazilian constitutional order, brought by the Brazilian Federative Republic Constitution of 1988, particularly in its 3rd article, becomes essentials fulfill the necessity of electric supply of the Amazon Isolated Systems and implement the regulatory acts developed to promote the economic progress of the north region of Brazil, a fair and just society and to diminish the Brazilian regional economic and social discrepancies. The politics of subsidies today implemented to allow the access of the north region populations and its industries to electric energy, especially the Conta de Consumo de Combustíveis dos Sistemas Isolados (CCC-ISOL), nevertheless fundamental to the achievement of the republicans objectives, represents a great cost to society, considering the cross-subsidies inefficiencies, the inexistence of a complete legal base to some political actions. Otherwise, the perspective of the implementation of key projects in the region, as the interconnection with the national grid, the construction of Hydro Power Plants in the Madeira river and the introduction of natural gas in Manaus, is taking away the spotlight in the CCC costs discussion. The present work, studying the current structure and the legal aspects of the Isolated Systems subsidies, propose measures to reduce the subsides inefficiencies in the CCC.